Learning Trajectories of High-Performance Teacher-Coaches in Japanese High Schools: A Mixed-Methods Study - Seita Kuki; Clifford J. Mallett; Jun Mizushima; Steven B. Rynne (CV. FOUNDAE, 2025)
Background: Understanding how effective coaching impacts athlete success is crucial to understanding how high-performance teacher-coaches manage their dual teaching and coaching roles and develop their professional skills throughout their careers.Aim: This study examined the key learning sources contributing to the professional development of teacher-coaches in Japan.Methods: This study adopted a mixed-methods approach involving eight male teacher-coaches with over 20 years of successful coaching experience. Participants completed a questionnaire rated on a 7-point Likert scale regarding the importance of various learning sources throughout their careers. Additionally, semi-structured interviews were conducted to gain an in-depth understanding of their learning experiences.Results: Quantitative analysis showed that the learning sources changed across career phases: